High Policy Analysis From the Copenhagen School Perspective : The Securitization of the Post-Cold War Climate Crisis - GEZER, SELEN (İstanbul Kültür Üniversitesi, 2023)
The groundbreaking discovery in 1896 by renowned chemist Svante Arrhenius, which established a link between greenhouse gas emissions and atmospheric changes, marked a significant turning point in research on the human-induced origins of the climate crisis. A century later, as the effects of the Cold War began to shape international relations, the Climate Crisis transitioned from being perceived as a low-policy issue to a high policy priority. Advancements in technology and scientific studies led to a collective agreement among experts, with the United Nations taking the lead in addressing these challenges. Since the 1990s, the climate crisis has evolved into not only an environmental problem but also a global social and ecological crisis that necessitates a reevaluation of global political and economic systems. Addressing the causes and consequences of the climate crisis requires a global perspective and a security-oriented approach. Greenhouse gas emissions, which contribute to the greenhouse effect, are a worldwide phenomenon and thus constitute a global problem, albeit with significant regional variations that need to be understood. This research examines the link between the climate crisis and security through a multidisciplinary approach, investigating the causes of framing climate issues as urgent security concerns.
▪ Yüksek lisans tezi.
Keywords: Climate Crisis; Copenhagen School; Securitization; Global Security; Environmental Law; Post-cold War; High Political Concerns